Geographies of absences (Praxis Educativa, 2016)
The reason of visualizing, in the territory, the historical subalterinization of social groups for their class, ethnicity, sexual identity, relations with the “development”, absences and silences, responds to an ethical and political interest in re- signifying the senseof academic knowledge, legitimizing it in the teaching of Geography. In this article, some lines of understanding are synthesized, which are included in the practice of Geography of Latin America, subject of the Teacher’s Program and Bachelor’s Degree in Geography, School of Human Sciences (UNLPam).
Keywords: territory; patriarchy; colonialism; capitalism